Model testing of upright and tapered suction caissons in sand. (2nd January 2016) - Zeinoddini, M.; Kakasoltani, S.; Abdi, M.R.; Ahmadi, I.
Abstract : Behaviour of upright suction caissons with regard to their applications, installation, load-bearing, etc., has already been investigated by a number of researchers. Some researchers have also addressed the behaviour of tapered piles under different loading conditions. However, there has not been any previous experimental experience regarding the performance of tapered suction caissons. This paper reports the results of a primarily experimental investigation intended as a first step to understanding the performance of tapered suction caissons. The 1g experiments have been carried out on small-scale caisson models having upright and sloping walls. The caissons have been installed in a very fine saturated silty sand, and the effects of geometrical parameters, wall slope and the soil density on the overall penetration force required for installation and the pull-out capacity of the cassion have been studied. Influence of pull-out rate on the ultimate capacities has also been investigated.